Validation of the Humor Style Questionnaire with university students - Cassaretto, Mónica (2009)
This study validates the Humor Style Questionnaire in a group of 315 university students of both genders from Lima, Peru, with an average age of 19,7. The Humor Style Questionnaire (HSQ) by Martin, Puhlik-Doris, Larsen, Gray & Weir (2003), the Psychological Well-Being Scale (BIEPS-A) by Casullo (2002) and the Hope Scale by Herth (1991) were used. After the neutralization of four items, results show reliability coefficients between 0,64 to 0,78 and a factorial structure confirming the existence of four factors (42,94% of the total variance).Results show positive associations between psychological well-being and hope with affiliation and self-enhancing styles, and negative associations between aggression and self-defeating humor. Results support the convergence validity and the construct of the scale.